Overview of Trauma Injuries Caused by Traffic Accidents in Baixada Santista, Brazil (Epidemiology, Biostatistics, and Public Health, 2024)
Background: In Brazil, traffic accidents have been on the rise. There is a very high social and economic impact in the country, either by the direct sequelae that are left by the trauma, or by the deaths caused by it. Objective: This study aims to analyze the medical care associated with traffic accident-induced trauma in Baixada Santista, a Brazilian region comprising nine cities (six of which were included in this paper), along with the causes and consequences of such incidents for the population. Methods: For data collection, DATA SUS BRASIL, which is a governmental website, was used. The impact that trauma causes on people and the main bodily injuries produced in them, the most affected groups and the cities of the Baixada Santista where the accidents occurred were collected. The data were analyzed using descriptive statistics / relative frequencies. Results: The analysis reveals that young men, particularly those who ride motorcycles, are most susceptible to traffic accidents. In relation to the cities of the Baixada Santista, we verified that the city of Santos emerges as the primary location for these accidents, primarily due to its substantial motorcycle fleet. Conclusions: There is a pressing need to implement preventive measures targeting young male motorcyclists in this region. It is through awareness that it will be possible to act in the prevention of accidents and reinforce to the public power, not only the need for consciousness, but also the importance of qualifying the nurses and professionals involved in the treatment and rescue of victims.
Keywords: trauma; traffic accident; prevention; traffic injuries